Superparamagnetic Iron Oxide Particles (VSOPs) Show Genotoxic Effects but No Functional Impact on Human Adipose Tissue-Derived Stromal Cells (ASCs) - Radeloff, Katrin (Materials (Basel), 2021)
Adipose tissue-derived stromal cells (ASCs) represent a capable source for cell-based therapeutic approaches. For monitoring a cell-based application in vivo, magnetic resonance imaging (MRI) of cells labeled with iron oxide particles is a common method. It is the aim of the present study to analyze potential DNA damage, cytotoxicity and impairment of functional properties of human (h)ASCs after labeling with citrate-coated very small superparamagnetic iron oxide particles (VSOPs). Cytotoxic as well as genotoxic effects of the labeling procedure were measured in labeled and unlabeled hASCs using the MTT assay, comet assay and chromosomal aberration test. Trilineage differentiation was performed to evaluate an impairment of the differentiation potential due to the particles. Proliferation as well as migration capability were analyzed after the labeling procedure. Furthermore, the labeling of the hASCs was confirmed by Prussian blue staining, transmission electron microscopy (TEM) and high-resolution MRI. Below the concentration of 0.6 mM, which was used for the procedure, no evidence of genotoxic effects was found. At 0.6 mM, 1 mM as well as 1.5 mM, an increase in the number of chromosomal aberrations was determined. Cytotoxic effects were not observed at any concentration. Proliferation, migration capability and differentiation potential were also not affected by the procedure. Labeling with VSOPs is a useful labeling method for hASCs that does not affect their proliferation, migration and differentiation potential. Despite the absence of cytotoxicity, however, indications of genotoxic effects have been demonstrated.